A Genetic Transformation Method for Cadmium Hyperaccumulator Sedum plumbizincicola and Non-hyperaccumulating Ecotype of Sedum alfredii - Liu, Huan; Zhao, Haixia; Wu, Longhua; Xu, Wenzhong (Frontiers in Plant Science, 2017)
The present study demonstrates the development of an Agrobacterium-mediated genetic transformation method for species of the Sedum genus, which includes the Cd/Zn hyperaccumulator S. plumbizincicola and the non-hyperaccumulating ecotype of S. alfredii. Multiple shoots were induced from stem nodes of two Sedum plants using Murashige and Skoog (MS) medium containing 0.1 mg/L cytokinin 6-benzyladenine (6-BA) and 1.0 mg/L auxin 1-naphthaleneacetic acid (NAA). The shoot primordia were used as direct targets for Agrobacterium infection. Selection on hygromycin was highly effective in generating Agrobacterium-transformed explants. This callus-free procedure allowed us to obtain transgenic plantlets after rooting hygromycin-resistant shoots on phytohormone-free MS medium containing the antibiotic. The presence and expression of the reporter genes gusA and GFP in transgenic plants were confirmed by a real-time polymerase chain reaction (PCR), histochemical GUS assays, and confocal microscopy. This reliable method for genetic transformation of Sedum plants will help us to understand gene functions and the molecular mechanisms underlying Cd hypertolerance and hyperaccumulation in these species.